Precise diagnosis and targeted therapy of nodal T-follicular helper cell lymphoma (T-FHCL) - Du, Jun; Jin, Shikai; Zhang, Minghui; Fu, Xuehang; Yang, Jingwen; Zhang, Liwen; Chen, Zhenwei; Huang, Zoufang; Li, Weisong; Hou, Jian; Wang, Ting (Frontiers in Oncology, 2023)
Nodal T-follicular helper cell lymphoma (T-FHCL) derived from T-follicular helper (Tfh) cell falls into a heterogeneous category of peripheral T-cell lymphoma (PTCL). Due to the limited number of therapeutic regimens and limited first-line efficacy, T-FHCL has a poor prognosis, and there is an urgent need for effective targeted therapies. With advancements in sequencing technologies, especially single-cell sequencing and next-generation sequencing, more specific genetic aberrations characteristic of T-FHCL can be discovered, allowing for precise molecular diagnosis and specific research on novel agents. Many biomarker-targeting agents, used either alone or in combination, have been tested, and they have generally enhanced the therapeutic outcomes of T-FHCL. Histone deacetylase inhibitors achieve significant clinical benefits in the treatment of T-FHCL, especially in combination therapy. Chimeric antigen receptor T-cell (CAR-T-cell) immunotherapies, hematopoietic stem cell transplantation, and other potential agents merit further study.